2021
DOI: 10.1093/mnras/stab3036
|View full text |Cite
|
Sign up to set email alerts
|

The formation of massive stellar clusters in converging galactic flows with photoionization

Abstract: We have performed simulations of cluster formation along two regions of a spiral arm taken from a global Milky Way simulation, including photoionising feedback. One region is characterised by strongly converging flows, the other represents a more typical spiral arm region. We find that more massive clusters are able to form on shorter timescales for the region with strongly converging flows. Mergers between clusters are frequent in the case of the strongly converging flows and enable the formation of massive c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 76 publications
2
38
0
Order By: Relevance
“…Motivated by recent numerical and observational findings (e.g., Kim et al 2018b;Tsuge et al 2021), we simulated the formation of a massive compact cluster via the collision of two GMCs, each weighing 3.6 × 10 5 M e , using RHD simulations. In particular, we focused on the impact of radiation feedback on the formation process of GC candidates and found that it can play an important role in determining the star formation histories, stellar masses, and metallicity distributions (see also Dobbs et al 2022). Our results are summarized as follows.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Motivated by recent numerical and observational findings (e.g., Kim et al 2018b;Tsuge et al 2021), we simulated the formation of a massive compact cluster via the collision of two GMCs, each weighing 3.6 × 10 5 M e , using RHD simulations. In particular, we focused on the impact of radiation feedback on the formation process of GC candidates and found that it can play an important role in determining the star formation histories, stellar masses, and metallicity distributions (see also Dobbs et al 2022). Our results are summarized as follows.…”
Section: Discussionmentioning
confidence: 92%
“…We present one of the first studies that attempt to understand the impact of radiation feedback on the formation of massive compact clusters using RHD (see also Dobbs et al 2022). However, several caveats should be considered when interpreting our results.…”
Section: Caveatsmentioning
confidence: 94%
See 1 more Smart Citation
“…Simulations can take into account of surrounding gas by resimulating, or zooming in on small sections of whole galaxy simulations (Van Loo et al 2013;Smilgys & Bonnell 2017;Bending et al 2020;Ali 2021;Rieder et al 2022;Smith et al 2020;Dobbs et al 2022). Dobbs et al (2022) showed that colliding flows on larger scales are significant in determining the final cluster mass, partly because they lead to more mergers between clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations can take into account of surrounding gas by resimulating, or zooming in on small sections of whole galaxy simulations (Van Loo et al 2013;Smilgys & Bonnell 2017;Bending et al 2020;Ali 2021;Rieder et al 2022;Smith et al 2020;Dobbs et al 2022). Dobbs et al (2022) showed that colliding flows on larger scales are significant in determining the final cluster mass, partly because they lead to more mergers between clusters. Generally, simulations show that at least for the formation of more massive clusters, cluster formation is hierarchical and mergers are frequent (Bonnell et al 2003;Smilgys & Bonnell 2017;Fujii & Portegies Zwart 2015;Fujii et al 2021;Guszejnov et al 2022;Dobbs et al 2022).…”
Section: Introductionmentioning
confidence: 99%